Corporate board gender diversity and ethnic ownership of U.S. - Yunsun Huh; Russell Kashian (Journal of Applied Economics, 2021)
This study examines the association between U.S. banks' corporate board gender and ethnic ownership diversity, focusing on cultural gender norms relating to female leadership positions. Utilizing Federal Deposit Insurance Corporation (FDIC) Call Report and Summary of Deposit (SOD) data for 30 June 2018 and American Community Survey data for 2017, we analyze 136 Minority Depository Institutions (MDIs) and their matching sample of mainstream banks in the U.S. We find differential effects on both the gender composition of MDI corporate boards and the probability of having female members on corporate boards depending on the ethnic diversity of bank ownership. Black-owned banks show a strong positive impact, while Hispanic-owned banks show a strong negative impact, regarding board gender diversity, relative to mainstream banks. These results demonstrate the relationship between cultural gender norms and female leadership access across different ethnicities in the U.S. banking industry.
Keywords: 330; Board gender diversity; women's leadership access; ethnic diversity; minority owned banks